READ THIS FOR ‘GUARANTEED RESULTS’: a feminist analysis of masculinity, health, and body through a case study of gym-bros and fit-fluencers - Wood, Rachael Leigh (Kansas State University, 2024)
Modern fitness has shifted with the rise of social media platforms like TikTok. The accessibility and interactive nature of visual platforms has allowed for “gym-bros” and “fit-fluencers,” as well as everyday gym goers to share their health and fitness journeys, work-out advice, and “transformation” (i.e., physical body changes) videos. The current exploratory sociological research project is in pursuit of understanding how masculinity, body, and health are discussed on TikTok, Reddit, Instagram, and YouTube. Feminist theory, in particular, intersectionality helps to highlight not just race, class, gender, but injuries, disabilities, and health/body conditions. Results and conclusions include how gym-bros and fit-fluencers, as well as everyday users on GymTok present themselves online, the relations that emerge out of this space, and the collective, unified shared experiences in the fitness community. The sentiments of “gains,” “anything is possible,” and “guaranteed results” purported by fitness community members online are embedded in neoliberal ideologies of self-responsibility and individualism. This research project provides insight into how GymTok and other social media platforms facilitate dialogues around body, health, and overall well-being.
Keywords: Health; Masculinity; Body; Social media; Fitness; Feminist research